C0818, a novel curcumin derivative, interacts with Hsp90 and inhibits Hsp90 ATPase activity - Yingjuan Fan; Yang Liu; Lianru Zhang; Fang Cai; Liping Zhu; Jianhua Xu (Acta Pharmaceutica Sinica B, 2017)
The aims of the present study were to estimate the affinity between 3,5-(E)-bis(3-methoxy-4-hydroxybenzal)-4-piperidinone hydrochloride (C0818) and heat shock protein 90 (Hsp90) and to investigate the inhibitory effects of this compound on Hsp90 ATPase activity. Fluorescence spectroscopy was used to examine the affinity between varying concentrations of C0818 and Hsp90, N-Hsp90, M-Hsp90 and C-Hsp90. Fluorescence intensities were recorded in the range of 290–510 nm at 293, 303 and 310 K, respectively. A colorimetric assay for inorganic phosphate (based on the formation of a phosphomolybdate complex and the subsequent reaction with malachite green) were used to examine the inhibitory effects of C0818 on Hsp90 ATPase activity. The equilibrium dissociation constant KD value of C0818 was found to be 23.412±0.943 μmol/L. The interaction between C0818 and Hsp90 was driven mainly by electrostatic interactions. C0818 showed the strongest affinity with C-Hsp90. These results conclusively demonstrate the inhibitory activity of C0818 on the activity of Hsp90 ATPase.